Epic animal journeys - Brown, Ed J.; Hanaor, Ziggy (Cicada Books, 2023)
One of the great mysteries of the world is that all the branches of the animal kingdom - birds, fish, crustaceans, reptiles, mammals, insects, and even slime molds - undertake great journeys across water, land, or air. With no compass or GPS devices, birds fly thousands of miles from Europe to their African feeding grounds, salmon cross oceans so that they may return to the rivers in which they were born and monarch butterflies spend their entire adult lives traveling from the grasslands of the Midwest to the forests of Mexico.